2002
DOI: 10.1590/s1516-31802002000200003
|View full text |Cite
|
Sign up to set email alerts
|

Familial cancer aggregation and the risk of lung cancer

Abstract: CONTEXT: Around 90% of lung cancer worldwide is attributable to cigarette smoking, although less than 20% of cigarette smokers develop lung cancer. Other factors such as diet, chronic lung diseases, occupation and possibly environmental agents also contribute to this cancer. Genetic factors seem to play a role in lung cancer, but the precise characteristics influencing lung cancer susceptibility are not known, since genetic factors are easily obscured by the strong environmental determinants of lung cancer, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…In all, 31 studies were identified that provided risks of lung cancer stratified by family history of the disease (Tokuhata and Lilienfeld, 1963a, b;Lynch et al, 1982;Ooi et al, 1986;Samet et al, 1986;Gao et al, 1987;Kramer et al, 1987;Sellers et al, 1987;Tsugane et al, 1987;Horwitz et al, 1988;Wu et al, 1988Wu et al, , 1996McDuffie et al, 1989;Wu-Williams et al, 1990;Liu et al, 1991;McDuffie, 1991;Osann, 1991;Shaw et al, 1991;Pavlakou et al, 1993;Schwartz et al, 1996Schwartz et al, , 1999Wang et al, 1996;Brownson et al, 1997;Kreuzer et al, 1998;Mayne et al, 1999;Bromen et al, 2000;Wunsch-Filho et al, 2002;Etzel et al, 2003;Wu et al, 2004;Jin et al, 2005;Matakidou et al, 2005). Three studies (Lynch et al, 1982;Sellers et al, 1987;Schwartz et al, 1999) were excluded from the review as the same data were duplicated in subsequent studies.…”
Section: Case -Control Studiesmentioning
confidence: 99%
“…In all, 31 studies were identified that provided risks of lung cancer stratified by family history of the disease (Tokuhata and Lilienfeld, 1963a, b;Lynch et al, 1982;Ooi et al, 1986;Samet et al, 1986;Gao et al, 1987;Kramer et al, 1987;Sellers et al, 1987;Tsugane et al, 1987;Horwitz et al, 1988;Wu et al, 1988Wu et al, , 1996McDuffie et al, 1989;Wu-Williams et al, 1990;Liu et al, 1991;McDuffie, 1991;Osann, 1991;Shaw et al, 1991;Pavlakou et al, 1993;Schwartz et al, 1996Schwartz et al, , 1999Wang et al, 1996;Brownson et al, 1997;Kreuzer et al, 1998;Mayne et al, 1999;Bromen et al, 2000;Wunsch-Filho et al, 2002;Etzel et al, 2003;Wu et al, 2004;Jin et al, 2005;Matakidou et al, 2005). Three studies (Lynch et al, 1982;Sellers et al, 1987;Schwartz et al, 1999) were excluded from the review as the same data were duplicated in subsequent studies.…”
Section: Case -Control Studiesmentioning
confidence: 99%
“…39 From the pioneering study of Tokuhata & Lilienfeld 32 on familial aggregation of lung cancer, several studies have consistently demonstrated an increased prevalence of cancer among relatives of lung cancer patients. Table 1 shows data on smoking from a case-control study 40 and as can be noted, cigarette smoking has distinct effects on those with or without reported cancer cases in first-degree relatives. A joint effect was detected 40 with permission **Parents and siblings ***Odds ratio adjusted for gender, age and socio-economic status (four levels) ****95% confidence interval between the variables smoking and cancer in relatives on the risk of lung cancer.…”
Section: Environment and Genetic Factors In Cancermentioning
confidence: 99%
“…Table 1 shows data on smoking from a case-control study 40 and as can be noted, cigarette smoking has distinct effects on those with or without reported cancer cases in first-degree relatives. A joint effect was detected 40 with permission **Parents and siblings ***Odds ratio adjusted for gender, age and socio-economic status (four levels) ****95% confidence interval between the variables smoking and cancer in relatives on the risk of lung cancer.…”
Section: Environment and Genetic Factors In Cancermentioning
confidence: 99%
“…The identification of at-risk populations will allow resources to be concentrated on early detection, with an improvement in outcomes. The well-structured article by Wünch-Filho et al 5 in this issue adds new evidence to the concept of genetic risk factors for lung cancer. …”
mentioning
confidence: 97%